Distribution of temperature, salinity and density in the Arabian sea along the South Malabar coast (South India) during the post-monsoon season - Rama Sastry, A A; Myrland, P (Indian Journal of Fisheries, 2016)
Physical oceanographic investigations form an important part of an integrated marine fisheries research programme. The Central Marine Fisheries Research Station in co-operation with the Indo-Norwegian Project has initiated a detailed oceanographic programme during the year 1957-58 in the waters off the Kerala Coast in order to obtain a detailed knowledge of the various Physical Oceanographic parameters in the Arabian Sea and their possible variations both in time and space.